2022
DOI: 10.1002/ece3.9347
|View full text |Cite
|
Sign up to set email alerts
|

Conserving diversity in Irish plant–pollinator networks

Abstract: Beneficial insects provide valuable services upon which we rely, including pollination. Pollinator conservation is a global priority, and a significant concern in Ireland, where over half of extant bee species have declined significantly in recent decades. As flower‐visiting insects rely on flowering plants, one way to conserve and promote pollinator populations is to protect high‐quality habitat. We analyzed the structure of insect–flower interactions from multiple habitat categories in a large database of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…8). Thirty surveys were completed in this way and while the results were not robust enough for statistical analysis, they did support the findings of Russo et al (2022) in that R. fruticosus agg. was most frequently interacted with (209 interactions).…”
Section: One Size Does Not Fit All: Recommendations For Pollinating I...mentioning
confidence: 78%
See 1 more Smart Citation
“…8). Thirty surveys were completed in this way and while the results were not robust enough for statistical analysis, they did support the findings of Russo et al (2022) in that R. fruticosus agg. was most frequently interacted with (209 interactions).…”
Section: One Size Does Not Fit All: Recommendations For Pollinating I...mentioning
confidence: 78%
“…In the case of livestock farms, enriching the diversity and quantity of ground flora is pivotal for attracting and supporting solitary bees (Potts et al 2010). Recent work examining the plant-pollinator networks in Ireland found that, unlike in many other contexts, the networks in Irish agricultural landscapes are highly asymmetrical, with more plant species than pollinators (Russo et al 2022). However, the many non-native plant hosts present on agricultural land were shown not to be attractive to pollinators.…”
Section: One Size Does Not Fit All: Recommendations For Pollinating I...mentioning
confidence: 99%
“…Boraginaceae, and Plantago lanceolata , L. Plantaginaceae). These comprised six native perennial and one non-native annual herbaceous species ( P. tanacetifolia ), selected as pollinator-attractive ( Clifford, 1962 ; Russo et al, 2022 ), and likely to be found on agricultural field edges in Europe. They represent a diverse group of plant families with regard to floral resource quality ( Ruedenauer et al, 2019b ; Vaudo et al, 2020 ; Zu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%